2012
DOI: 10.1093/humrep/des210
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pronuclei morphology and dynamicity on live birth outcome after time-lapse culture

Abstract: The PN morphology changes over time, indicating that the single light microscopy observation approach is deficient in comparison to time-lapse. Although the assessment of the PN morphology does not improve embryo selection, the timing of PNB should be included in embryo selection parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 31 publications
6
87
2
Order By: Relevance
“…Our results were comparable with those given in the literature [11,18]. It makes us presume that Esmya does not have adverse effect on the quality of egg cell produced.…”
Section: Case Reportsupporting
confidence: 91%
“…Our results were comparable with those given in the literature [11,18]. It makes us presume that Esmya does not have adverse effect on the quality of egg cell produced.…”
Section: Case Reportsupporting
confidence: 91%
“…Similar reports have linked with high sensitivity and specificity the use of TLM with the ability of prediction of the cleavage stage embryos and their potential to reach the blastocyst stage, resulting in increased live births [12,16,19,26,31,34,39,41]. On the other hand, other reports showed that TLM parameters are not able to predict live birth when compared with the conventional methods [33,34,42].…”
Section: Discussionmentioning
confidence: 70%
“…In the present study, the pronuclear morphology was evaluated at 16-18 h after ICSI. Recent data using time-lapse imaging demonstrated that the pronuclear morphology changes over time, indicating that the single light microscopy observation approach is deficient in comparison to time-lapse [27]. Therefore, our findings must be confirmed by future trials, if possible using time-lapse imaging technology.…”
Section: Discussionmentioning
confidence: 70%
“…Previous time-lapse observations evaluating the pronuclear morphology [27], suggests that the number and distribution of NPBs does not predict the quality of the zygote, in terms of live birth potential. Despite this, these morphological features have been chosen as a quality indicator of the fertilized oocyte.…”
Section: Discussionmentioning
confidence: 91%